Two Sides of a Medal: The Changing Relationship between Religious Diversity and Religiosity - Matthias Opfinger (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2013)
Religious Market Theory assigns basic market principles to the market for religion. The derived supply side model proposes that religiosity is higher on a competitive market, characterized by high religious diversity. Churches will provide higher quality goods compared to monopolistic churches. The demand side model, originating from the Secularization Hypothesis, suggests that the establishment of new churches casts doubt on the existing religion, which reduces overall religiosity. I find a negative linear relationship between religious diversity and religiosity which supports the demand side model. However, high levels of income, education, and democracy mitigate this effect. The relationship becomes positive in the most developed countries. The demand side model seems to dominate in less developed countries, while the supply side model better describes the market for religion after Secularization has occurred.
Keywords: D4; O1; Z12; 330; Supply side; Demand side; interaction; attenuating effects